"Hoje é dia, mais uma vez, de mudar de casa e de vida": exílio, ficção e história em contos de Caio Fernando Abreu - Souza, Antônio João Galvão de (2017)
The present work is a study of the exile literary images in four Caio Fernando Abreu??s short stories written and/or published between 1974 and 1977: ―Lixo e purpurina‖, ―London, London ou Ajax, brush and rubbish‖, ―Paris não é uma festa‖ and ―Holocausto‖. These impressions and images of the exile are apprehended as from a theoretical discussion around the relations between literature and history, which conducted to the perception of a specific literary procedure for the fictional representation of the exile experience in this short story writer, presently proposed as a narrativity of the exile in the short stories analyzed. Thus, our objectives comprehend a discussion about the general theoretical subsidies of the imbrications amongst literature, history, society and authoritarianism in Brazil during the military dictatorship; infer critical and theoretical instances about the relations between exile and literature; as well as discuss and analyze the modes through which this interdisciplinary theoretical background culminates in a specific narrativity of the exile in these short stories, as from which the following characteristics were detected: a) the usage of a literary language as a perceptive act of the exile??s images and impressions; b) the narrative structure in fragments; c) the complex symbiosis between reality and fiction and, for this reason, the short story as a text to problematize the register of a period and of a fact provided by history; d) the various non-linear time lines which cross the interior of the narrative; e) the verb tenses of the short stories eminently in the present. Therefore, this work is based on theoretical and critical contributions of the main national and foreign authors whose researches are based upon the relations between the literary representation of the exile and history. The bibliographical data collected, which led to the distinction of a narrativity of the exile in these four texts, pointed out the dilution of the referential notions of the historical reality as well as symbologies and specific literary impressions of the exile emerging from the short stories.